2015
DOI: 10.1371/journal.pone.0133926
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Tight Junctions and Enhancement of Barrier Integrity of the CACO-2 Intestinal Epithelial Cell Layer by Micronutrients

Abstract: The micronutrients zinc, quercetin, butyrate, indole and berberine were evaluated for their ability to induce remodeling of epithelial tight junctions (TJs) and enhance barrier integrity in the CACO-2 gastrointestinal epithelial cell culture model. All five of these chemically very diverse micronutrients increased transepithelial electrical resistance (Rt) significantly, but only berberine also improved barrier integrity to the non-electrolyte D-mannitol. Increases of Rt as much as 200% of untreated controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 47 publications
10
88
3
3
Order By: Relevance
“…Our conclusion here arises from the epithelial cell model and is limited to the dynamic of TJs reassembly regulated by NaB. On the other hand, Valenzano et al showed that after Caco-2 cell layers were cultured for 72 h with butyrate, protein expression of claudin-2 decreased 90% and that of claudin-7 increased 376% [43], suggesting butyrate might also regulate the remodeling of the TJs complex along with the differentiation state of Caco-2 cells for maturing the barrier function.…”
Section: Discussionmentioning
confidence: 94%
“…Our conclusion here arises from the epithelial cell model and is limited to the dynamic of TJs reassembly regulated by NaB. On the other hand, Valenzano et al showed that after Caco-2 cell layers were cultured for 72 h with butyrate, protein expression of claudin-2 decreased 90% and that of claudin-7 increased 376% [43], suggesting butyrate might also regulate the remodeling of the TJs complex along with the differentiation state of Caco-2 cells for maturing the barrier function.…”
Section: Discussionmentioning
confidence: 94%
“…TER of 8-day-old Caco-2 cells (5 days after confluence) was measured at 24 h intervals for 48 h in total. Partially differentiated Caco-2 monolayer was used to imitate the intestinal conditions comprising of enterocytes still in the process of maturation and prone to changes of barrier integrity due to external stimuli (Reunanen et al, 2015; Valenzano et al, 2015). Sutterella spp.…”
Section: Resultsmentioning
confidence: 99%
“…An understanding of the regulatory pathways of Cldn2 expression is of significant interest because its expression is increased in IBD, celiac disease, and HIV enteropathy and colonic cancer (20). It is noteworthy that butyrate has been previously mentioned in the regulation of Cldn2 (38, 53), without insight into mechanism. The present studies add significantly to this work and identify a role for butyrate-dependent IL-10R signaling in the repression of Cldn2.…”
Section: Discussionmentioning
confidence: 99%